A Rare Cutaneous Malignancy: A Primary Cutaneous Carcinosarcoma with Adnexal Epithelial Component (Trichoblastic Carcinosarcoma) of Left Temporal Region - Vaishali B. Nagose; Sachin S. Ingle; Nilesh O. Chandak; Shirish R. Gondane (Indian Journal of Dermatology)
Primary cutaneous carcinosarcoma (PCCS) is a rare cutaneous biphasic tumour with just 120 cases being reported till date. The epithelial component trichoblastic carcinoma/ malignant trichoblastoma (trichoblastic carcinosarcoma) is even rarer, so is the present case. An eighty years old male patient presented with a rapidly progressing ulceroproliferative nodular growth on the left temporal region. The incisional biopsy showed primary cutaneous carcinomasarcoma (PCCS). IHC showed epithelial and stromal component marked exclusively for pancytokeratin (AE1/AE3) CK5&6/ p40 and vimentin respectively. Both components were immunopositive for D2-40 and immunonegative for BerEP4/ S100/ Melan A/ MITF, thus final diagnosis given was Trichoblastic carcinosarcoma. Wide excision of the lesion with local rotation flap and skin grafting (thigh skin) was done. Patient remains disease free after four years also. Present case thus highlights the importance of HPE, IHC and early surgery for excellent prognosis of PCCS.